Sistem Pendukung Keputusan Pemilihan Pembersih Wajah Terbaik Dengan Menerapkan Metode ELECTRE - Handayani, Tuti (Bulletin of Data Science, 2023)
Facial cleanser is one type of skincare product used to remove residual dirt and dust that adheres to the skin. Additionally, it serves to cleanse and refresh the skin. The face is an external part of the body that never escapes the attention of individuals, especially women, who are concerned with beauty. The face is a source of attraction and boosts the confidence of anyone with beautiful and appealing skin. Various skincare products, with a wide range of choices, are preferred by many women to achieve radiant, beautiful, and fair skin. The use of a decision support system to make informed choices is expected to address the challenges faced by both women and men when selecting facial cleansers. In this Decision Support System, the researcher applies the Electre method. Based on the calculation of recommended assessment criteria fed into the system, the selection of the best facial cleanser is determined by calculating the priority weights for alternative choices of facial cleansers.